Clinical and Subclinical Distress, Quality of Life, and Psychological Well‐Being after Cardiac Rehabilitation. Issue 3 (24th November 2017) - Gostoli, Sara; Roncuzzi, Renzo; Urbinati, Stefano; Rafanelli, Chiara
Abstract : Background: The literature has outlined positive effects of cardiac rehabilitation (CR) on clinical psychological distress (DSM depression and anxiety) and quality of life (QoL). In cardiac settings, subclinical distress (subthreshold depressive and anxious symptomatology) and psychological well‐being also showed relevant clinical implications. This research explored these psychological variables, their changes over time and cardiac course of CR patients. Methods: Clinical and subclinical distress, QoL, and psychological well‐being were assessed in 108 consecutive patients undergoing CR, at baseline and up to 12 months after the program's completion. Results: Of all patients, 25.9 per cent showed high distress with a DSM diagnosis, 31.5 per cent high distress without a DSM diagnosis, and 42.6 per cent low distress. Comparing these subgroups, worse QoL and psychological well‐being were significantly linked not only to clinical but also to subclinical distress. After CR completion, a significant reduction in DSM diagnoses was observed, whereas there were no positive effects on subclinical distress, QoL, and well‐being, or when they initially occurred, they were not long lasting. Moreover, only the subgroup with high distress without a DSM diagnosis was at greater risk for adverse cardiac outcomes, showing worse scores on items of contentment. Conclusions: These findings confirm data on clinical distress reduction after CR completion. However, a large amount of relevant subclinical distress remains and predicts adverse cardiac events.